INDONESIA'S DIPLOMATIC CONTRIBUTION TO THE ISRAEL-PALESTINE CONFLICT SINCE 1948 - Muhammad Irfan Gati; Abd. Hafid (Program Studi Hukum Tata Negara, Institut Agama Islam Negeri Parepare, 2024)
This article explores the dynamics of Indonesian diplomacy in the Israeli-Palestinian conflict. Despite ongoing tensions and armed confrontations between Palestinian fighters and the Israeli military, Indonesia has consistently advocated for Palestinian independence through a two-state solution. The historical ties between Indonesia and Palestine, coupled with the academic connections between Palestinian scholars and Indonesian students studying in Egypt, have strengthened the diplomatic relationship between the two nations. Indonesia's active role in supporting Palestinian recognition of Indonesian independence, alongside Egypt, remains relevant today. Using conflict resolution theory as a framework, this article delves into Indonesia's diplomatic efforts to address the Israeli-Palestinian conflict. Notably, Indonesia has actively participated as a non-permanent member of the UN Security Council, opposing policies such as US President Donald Trump's decision to recognize Jerusalem as the capital of Israel and relocate the embassy there. The findings illustrate Indonesia's multifaceted role in conflict resolution, encompassing positions as a co-sponsor, facilitator, mediator, participant, initiator, actor, motivator, and justifier in its endeavors to help resolve the Israeli-Palestinian conflict. By presenting these insights, the article aims to contribute to the understanding of Indonesia's unique diplomatic contributions to the ongoing conflict while avoiding plagiarism.